EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA NASTAR BERBASIS ANDROID TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR - Fauziah, Jihan; Alkhila Saira Putri, Hefna; Faizul Muna, Noor; Nurul Syafaah, Weduri; Setiawaty, Rani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension skill is a fundamental ability that needs to be developed from the elementary school level. However, observations at SD 4 Gondangmanis revealed that reading comprehension skills among fourth-grade students were still relatively low, attributed to the dominance of lecture-based methods and limited learning media. This study aims to determine the effectiveness of the Problem Based Learning (PBL) model assisted by Android-based NASTAR (Values in Literary Texts) media on reading comprehension skills of fourth-grade elementary school students. The study employed a quantitative approach with a pre-experimental one group pretest-posttest design. The research subjects were 14 fourth-grade students at SD 4 Gondangmanis in the 2025/2026 academic year. The instruments used included reading comprehension tests with four indicators: understanding the concept of values, identifying types of values in texts, drawing conclusions from stories, and determining the application and benefits of values in texts. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, the Paired Sample T-Test, and the N-Gain test. The results showed an increase in the average student score from 44.29 on the pretest to 62.14 on the posttest, a difference of 17.85 points. The Paired Sample T-Test yielded a significance value of 0.019 (< 0.05), indicating a significant difference between the pretest and posttest. The N-Gain test produced an average score of 0.3559, categorized as moderate. Therefore, the PBL model assisted by android-based NASTAR media is proven to be moderately effective in improving the reading comprehension skills of fourth-grade elementary school students.